Pengaruh Promosi, Aksesibilitas dan Kualitas Pelayanan Terhadap Kepuasan Pengguna Jasa Penyeberangan Kempang di Desa Degong Kabupaten Karimun - Hermalia Susana; Bunga Paramita; Agriend Putra (Penerbit Jurnal Indonesia, 2026)
This study aims to analyze the effect of promotion, accessibility, and service quality on the satisfaction of Kempang ferry service users in Degong Village, Karimun Regency. The approach used is quantitative with a survey method through a questionnaire distributed to 133 respondents who are users of the Kempang service. The data were analyzed using multiple linear regression analysis with the help of IBM SPSS software version 29. The results show that simultaneously, the three independent variables (promotion, accessibility, and service quality) have a significant effect on user satisfaction with an Adjusted R Square of 0.816, meaning that 81.6% of the variation in satisfaction can be explained by the combination of these three variables, with the remaining 18.4% explained by other factors not examined in this study. However, partially, only service quality had a positive and significant effect on satisfaction, while promotion and accessibility did not show a significant effect. This indicates that reliable, responsive, and safe service quality is a key factor in shaping user satisfaction. This study provides managerial implications that satisfaction improvement can be optimized through continuous service quality improvement.